Nanostructured lipid system as a strategy to improve the anti-Candida albicans activity of Astronium sp - Bonifácio, Bruna Vidal [UNESP]; Ramos, Matheus Aparecido dos Santos [UNESP]; Silva, Patrícia Bento da [UNESP]; Negri, Kamila Maria Silveira [UNESP]; Oliveira Lopes, Érica de [UNESP]; Souza, Leonardo Perez de [UNESP]; Vilegas, Wagner [UNESP]; Pavan, Fernando Rogério [UNESP]; Chorilli, Marlus [UNESP]; Bauab, Taís Maria [UNESP] (International Journal Of Nanomedicine, 2015)
The genus Astronium (Anacardiaceae) includes species, such as Astronium fraxinifolium, Astronium graveolens, and Astronium urundeuva, which possess anti-inflammatory, anti-ulcerogenic, healing, and antimicrobial properties. Nanostructured lipid systems are able to potentiate the action of plant extracts, reducing the required dose and side effects and improving antimicrobial activity. This work aims to evaluate a nanostructured lipid system that was developed as a strategy to improve the anti-Candida albicans activity of hydroethanolic extracts of stems and leaves from Astronium sp. The antifungal activity against C. albicans (ATCC 18804) was evaluated in vitro by a microdilution technique. In addition to the in vitro assays, the Astronium sp. that showed the best antifungal activity and selectivity index was submitted to an in vivo assay using a model of vulvovaginal candidiasis infection. In these assays, the extracts were either used alone or were incorporated into the nanostructured lipid system (comprising 10% oil phase, 10% surfactant, and 80% aqueous phase). The results indicated a minimal inhibitory concentration of 125.00 µg/mL before incorporation into the nanostructured system; this activity was even more enhanced when this extract presented a minimal inhibitory concentration of 15.62 µg/mL after its incorporation. In vivo assay dates showed that the nanostructure-incorporated extract of A. urundeuva leaves was more effective than both the unincorporated extract and the antifungal positive control (amphotericin B). These results suggest that this nanostructured lipid system can be used in a strategy to improve the in vitro and in vivo anti-C. albicans activity of hydroethanolic extracts of Astronium sp.
Keywords: Anticandidal activity; Microdilution; Microemulsion; Plant extract; Vulvovaginal candidiasis